Between Land and Sea: Assessing Hunter-Gatherer Subsistence Practices and Cultural Landscapes in Southern Portugal during the Final Mesolithic. - Diniz, Mariana (Société Préhistorique Française, 2016)
The longstanding relationship between human groups and the sea continues to shape European culture today, as we can see from Eurostat data. A large proportion of the present-day population could be classified as maritime and the goals for Horizon 2020 reflect the major role of the sea in the contemporary economy, sciences and ways of life. Among the questions to be addressed when looking at the relationship between the last hunter-gatherer groups and the sea — which means assessing how the sea and coastal regions were used and explored — we can ask what role the sea played in the cultural matrix of these groups? In order to define some starting points for this analysis, it is important to briefly sum up some general assumptions relating to this subject: 1) along European coasts, Final Mesolithic hunter-gatherers were traditionally described as relying heavily on a maritime economy; a situation that is supposed to change with the Neolithisation process and the dominance of agro-pastoral and land-based economies. Therefore, a major breakdown in the long-term ’maritime relation’ is assumed to be related to cultural factors as part of a chronological process; when domesticates arrived the sea lost its dominance; 2) traditionally, maritime hunter-gatherer economies are generally defined as an Atlantic phenomenon and groups in the Mediterranean Basin are thought to be characterized by less dense occupation patterns and a less marked maritime character. Debating why this major difference arose and why maritime economies are environmentally dependent – not only on the distance from the sea, which is an expected dependency — but mainly on which is the nearest sea, is a question to be explored in this paper. This assumption raises the problem as to how coastal zones were defined during the Final Mesolithic and how the different coastal hunter-gatherer groups settled along European shorelines, considering that recent data point to clear asymmetries between North Atlantic and Mediterranean hunter-gatherers. Southern ...